Híbridos da classe amino-álcool-silicatos: avaliação das relações estrutura-atividade adsortiva com o corante aniônico rose bengal - Moura, André Luis Alves (2016)
The present work presents the synthesis, characterization as well as the application of the organic-inorganic hybrid materials. These materials were used as adsorptive systems to anionic dye Rose Bengal (RB). We used two different kinds of polyether for this work – Poly Ethylene Oxide (PEO) and Poly Prophylene Oxide (PPO) with average molecular weights of 500 and 400 g mol-1 and the 3-glycidoxypropyltrimethoxysilane (GPMS). Preliminary studies, demonstrated that of hybrid xerogels reach the maximum adsorption capactity (qt) of 542.82 mg g -1 for PEO500-GPMS and 58.77 mg g-1 for PPO400-GPMS at 25 o C. The concentration of the anionic dye RB decreases in aqueous medium in presence of hybrid xerogel (PEO and PPO) - kinetics and the adsorption equilibrium results obtained by in situ UV-vis. This work also discusses how the nature and swelling properties of the polyethers PEO and PPO, investigated by small-angle X-ray scattering (SAXS) and in situ SAXS measurements, affect the way PEO500-GPMS and PPO400-GPMS interact with the anionic dye, Rose Bengal. Furthermore, the effect of solvent and pH in the nanostructural behavior of amino-alcoholsilicate hybrids systems was investigated by in situ SAXS. The results pointed out different degree of water absorption by the hybrid matrices which the materials based on PEO present characteristics as hydrogel. This ability of the nanostructure to swell increases the adsorption capacity of the anionic species which the presence of hydrophilic/hydrophobic polyether PEO and PPO nature results in different capacities and mechanisms of RB adsorption. The distinct aspects from the PEO and PPO-based hybrid reflected in higher adsorptive capacity by PEO500-GPMS hybrid when compared to PPO400-GPMS, to incorporate the anionic chemical species RB in its structured hybrid network. The presence of the RB in both systems was demonstrated by changes in FTIR spectra, the partitioning coefficients (D) at different temperatures and the presence of endothermic event in DSC curves before and after the adsorption. In this work, new candidate adsorbents were synthesized in order to amplify the proposals for more selective adsorptive systems in the adsorption of organic species.